Implementasi layanan responsif bimbingan konseling Islam melalui konseling kelompok terhadap bullying - Sopiah, Pipih; Rahman, Imas Kania; Ahmad (Program Studi Magister Pendidikan Agama Islam, 2026)
This descriptive qualitative study aims to describe the implementation of responsive Islamic Guidance and Counseling services through group counseling to address verbal bullying among junior high school students in Jakarta. The subjects included a guidance counselor and six students identified as engaging in bullying behavior. Data were collected through observation, interviews, documentation, and counseling progress notes. The implementation followed five stages: formation, transition, core activities, value reinforcement, and reflective closure. In this process, counselors applied an integrative approach combining Cognitive Behavior Therapy (CBT) with Ibn Miskawaih’s moral therapy. This integration utilized self-monitoring, cognitive restructuring, and behavioral rehearsal, synthesized with Islamic values, tazkiyatun nafs (soul purification), anger management, and the cultivation of noble character (akhlak). Following the intervention, students demonstrated significant positive behavioral changes, particularly in emotional control, increased empathy, and improved social relationships with peers. This study concludes that responsive Islamic Guidance and Counseling, utilizing an integrative CBT and Ibn Miskawaih framework, contributes effectively to eliminating bullying behavior among students. Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi layanan responsif Bimbingan dan Konseling Islam melalui konseling kelompok dalam mengatasi perilaku perundungan verbal siswa SMP di Jakarta. Subjek penelitian terdiri dari guru BK dan enam siswa yang terindikasi melakukan perundungan. Data dikumpulkan melalui observasi, wawancara, dokumentasi, serta catatan perkembangan konseling. Proses pelaksanaan konseling kelompok mencakup tahap pembentukan, peralihan, kegiatan inti, penguatan nilai, dan penutup reflektif. Dalam praktiknya, guru BK menerapkan pendekatan integratif yang memadukan Cognitive Behavior Therapy (CBT) dengan terapi akhlak Ibnu Miskawaih. Integrasi ini dilakukan melalui teknik self-monitoring, restrukturisasi kognitif, dan latihan perilaku yang dikombinasikan dengan nilai Islami, tazkiyatun nafs, manajemen amarah, serta penanaman empati. Hasil penelitian menunjukkan adanya perubahan perilaku positif pada siswa, terutama dalam pengendalian emosi, peningkatan empati, dan perbaikan hubungan sosial. Penelitian ini menyimpulkan bahwa layanan Bimbingan dan Konseling Islam dengan pendekatan integratif CBT dan pemikiran Ibnu Miskawaih berkontribusi dalam mengeliminasi perilaku perundungan di lingkungan sekolah.